The Relationship Between the Parameters of the Electric and the Acoustic Signal with the Destruction of Concrete Under Cyclic Freeze-Thaw - Fursa T. V. Tatyana Viktorovna; Dann D. D. Denis Dmitrievich; Surzhikov A. P. Anatoly Petrovich; Petrov M. (2016, 2016)
Title screen